SUBOPTIMAL TARGET BLOOD PRESSURE CONTROL AND ITS ASSOCIATION WITH THE SOCIODEMOGRAPHIC AND CLINICAL PROFILES OF HYPERTENSIVES ATTENDING A TERTIARY LEVEL HOSPITAL IN ADDIS ABABA, ETHIOPIA - Bekele, Daniel Mengistu; Gary, Rebecca A; Goshu, Dejuma Yadeta; Yalew, Alemayehu Worku; Higgins, Melinda K (International Journal For Research In Health Sciences And Nursing, 2023)
Background: Hypertensives’ target blood pressure control remains suboptimal in many countries worldwide. Hence, determining patients’ factors affecting target blood pressure control is critical. Objective: The objective of the study was to examine hypertensives’ target blood pressure control and its associations with their sociodemographic and clinical characteristics. Methods: The study employed a cross-sectional design. For the face-to-face data collection with standardized questionnaires, 384 hypertensives attending a tertiary-level hospital were selected using a systematic random sampling technique. Descriptive statistics were used to determine the target blood pressure control status and bivariate chi-square test and binary logistic regression were used to identify factors significantly associated with the target blood pressure control. Results: The study consisted of nearly equal proportions of male (51.2%) and female (48.8%) participants with a mean age (±SD) of 53.61 ±12.34 years. Only 45.1% had achieved target blood pressure control. Absence of comorbidity (AOR = 1.911, 95% CI: 1.256, 2.908, p = .002), good medication adherence (AOR = 2.535, 95% CI: 1.078, 5.960, p = .033), and normal body mass index (AOR = 1.675, 95% CI: 1.094, 2.564, p = .018) were factors significantly associated with the achievement of the target BP control. Conclusion: Intervention targeting hypertensives’ body weight control, early comorbidity screening and management, and strict adherence to antihypertension medication may improve patients’ blood pressure control status and should be among the priority of the hypertension care clinic specialists’ team.